18 Cine-derived strain using the glasgowheart method. (18th April 2016) - Mangion, K; Gao, H; Radjenovic, A; Luo, X; Haig, C; Berry, C
Abstract : Background: The GlasgowHeart method is designed to overcome some limitations of currently available feature-tracking methods by incorporating all of the myocardial tissues using an in-house developed intensity-based b-spline deformable registration method. The aim of this pilot study was to ensure that peak circumferential strain (Ecc) estimation is feasible and reproducible with minimal intra- and inter- observer variability. Methods: 20 healthy volunteers underwent 1.5T CMR twice,  < 2 days apart. Mid- LV cine sequences, were analysed with the Glasgowheart software (Figure 1 ). Two observers independently analysed 40 short axis slices for inter-observer variability. One observer reanalysed the 40 short axis slices. Pearson correlation and Bland-Altman analysis were used. Results: 20 participants were used in the analysis (mean age ± SD 49.5 years (17.2) 50% male). Ecc measured on the first set of MRIs by the two observers was highly correlated (R = 0.915, p < 0.001) and in excellent agreement (mean difference = 0.01; 95% LoA: −0.01, 0.02). Repeated image analysis also disclosed a high degree of association in paired measurements of Ecc that was strongly correlated (R = 0.915, p < 0.001) and in excellent agreement (mean = 0.00; 95% LoA: −0.02, 0.01). Ecc measured in the second set of MRIs by 2 observers was well correlated (R = 0.937, p < 0.001) and in excellent agreement (mean = 0.00; 95% LoA: −0.016 and 0.021). The repeated image analysis at follow-up yielded Ecc that was well correlated (R = 0.942, p < 0.001) and in excellent agreement (mean = 0.00; 95% LoA: −0.009 and 0.009). There was no difference between the average global Ecc at different time points (p > 0.05). Conclusion: The GlasgowHeart method is a robust and reproducible method of assessing cine-derived circumferential strain. By tracking a higher proportion of voxels than the currently available feature tracking software, it has clear potential to provide a more accurate assessment of strain.